Cephalotoxins: A Hotspot for Marine Bioprospecting? - Gonçalves, Cátia; Costa, Pedro M. (Frontiers in Marine Science, 2021)
Molluscs provided one of the pioneering approved pharmaceuticals from the seas: the painkiller ziconotide, developed from an ω-conotoxin isolated from cone snails. As marine biotechnologists are turning towards the immense range of novel bioproducts from marine invertebrates, little attention has been given to cephalotoxins, a group of obscure proteinaceous toxins produced by the salivary glands of coleoids, i.e., octopuses, squids and cuttlefishes. These toxins, for which there is empirical evidence for acting as immobilisers at least against crustaceans, are proteinaceous substances among the many that comprise the venomous mixtures secreted by these animals. Despite the ecological and economical importance of cephalopods, little is known about cephalotoxins, beginning with the actual span of taxa that secrete them. Indeed, cephalopods are long suspected for producing specific toxins as part of their predation and defence mechanisms, making them a promising group of marine animals for the bioprospecting of novel compounds. Despite scant or absent toxicological or otherwise experimental evidence for their bioreactivity, advances in “omics” methods have shed some light in the molecular structure of cephalotoxins. There are reports of cephalotoxins being complex glycoproteins that take part in a myriad of novel compounds being produced by the salivary glands. Still, there is no consensus of cephalotoxins being a conserved form of proteins. As Blue Biotechnology and marine bioprospecting for novel bioreactives are gaining momentum, the present review will provide the state-of-the-art on cephalotoxins, highlighting old and new research and existing gaps in the current knowledge.